Filozof nauki czy teoretyk poznania? Przyczynek do badań nad poglądami Michaela Polanyiego - Zmyślony, Iwo (Filozofia Nauki, 2008)
Michael Polanyi’s philosophical ideas are interpret in various ways worldwide. In Poland the name remains (barely) listed among such philosophers of science as Thomas Kuhn and Paul Feyerabend, whereas English or German authors regard him rather as a theorist of knowledge and place aside Gilbert Ryle, Charles Sanders Peirce, Hans-Georg Gadamer or Maurice Merleau-Ponty. The aim of the paper is to describe typical ways of how Polanyi’s ideas are being currently received and to report his main statements. It is proceeded in four steps. After short biography of the author briefed in first point, second one sums up the content of all his main works, depicting thereby the evolution of his views. In third point receptions published in Polish, English and German literature are screened and discussed, focusing on issues of rationality, personal knowledge, tacit knowledge and tacit knowing. Fourth point states a problem of alleged holism and eclecticism as interpretative characteristics of Polanyi’s philosophical views.